2020
DOI: 10.1186/s40359-020-00430-4
|View full text |Cite
|
Sign up to set email alerts
|

How do mothers of adolescents with chronic pain experience their own quality of life?

Abstract: Background: Chronic pain is a major health problem globally with severe personal and economic consequences. Maternal chronic pain is associated with their children's pain. Family pain models and shared environmental aspects are important in the understanding of chronic pain among adolescents. Pain in itself impairs the quality of life (QoL). However, satisfaction in the aspects of health and functioning, social and economic, psychological, and family life will together constitute a person's subjective experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Additionally, it was guided by their perception of what constitutes as 'good' and socially desirable parenting behaviour which conveys a favourable image of positive parental behaviours including parental warmth, support, and adaptive coping in response to adversities (Bornstein et al, 2014). Parenting an adolescent with chronic pain was often very distressing as parents typically felt helpless due to not being able to alleviate their child's pain, which was a violation of the parenting role (Skarstein et al, 2020). Such parental distress is a normal response to a challenging situation, highlighting the importance of future pain research focussing on normalization of both adolescent and parental responses to pain and associated disability (Eccleston, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was guided by their perception of what constitutes as 'good' and socially desirable parenting behaviour which conveys a favourable image of positive parental behaviours including parental warmth, support, and adaptive coping in response to adversities (Bornstein et al, 2014). Parenting an adolescent with chronic pain was often very distressing as parents typically felt helpless due to not being able to alleviate their child's pain, which was a violation of the parenting role (Skarstein et al, 2020). Such parental distress is a normal response to a challenging situation, highlighting the importance of future pain research focussing on normalization of both adolescent and parental responses to pain and associated disability (Eccleston, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain exists within a social context (Williams & Craig, 2016), with the impact of adolescent chronic pain extending beyond the individual to family and peers (Forgeron et al, 2010;Jaaniste, Phupps, Lang, & Champion, 2013;Jordan, Eccleston, & Osborn, 2007). Individuals who parent an adolescent with chronic pain report low levels of healthrelated quality of life (Mano, Khan, Ladwig, & Weisman, 2011), restrictions in their social life and feelings of helplessness (Skarstein, Bergem, & Helseth, 2020), sleep disruption, (Meltzer & Moore, 2008) and elevated levels of stress, anxiety, and depression (Eccleston, Crombez, Scotford, Clinch, & Connell, 2004). Additionally, parents report feelings of helplessness regarding their inability to relieve their child's pain (Jordan et al, 2007), fear, lack of control, and believe their parenting skills are impaired (Baert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a high percentage of the parents in this study (41%) reported family pain. Earlier research has shown that persistent pain in parents may in uence pain attitudes and coping in adolescents and that persistent pain in parents is associated with pain in adolescents [10,51].…”
Section: Discussionmentioning
confidence: 99%
“…Parents can experience pain and high levels of stress, which may affect their HRQOL and ability as caregivers [10,11]. Previous studies have shown that pain in uences HRQOL negatively, especially in women [4,12], and that parents' pain and pain coping patterns may be adopted by their children and thereby in uence HRQOL of both parents and their children [10,13]. In parents of preschool children in the general population, low parental HRQOL is predicted by mental health problems, and families with at least one individual experiencing problems and in need of assistance, such as psychotherapy and parenting programmes, rated their HRQOL lower than families without these problems [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation